What is the effect of learning models and interests on study results? - Suratno Suratno; Rahmat Murboyono; Muazza Muazza; Devi Guspita (Jurnal Cakrawala Pendidikan, 2023)
This study aims to determine whether there is a significant influence between the learning model (NHT and STAD) and student interest on learning outcomes. This study uses a mixed methods approach with a sequential explanation. Sequential explanatory is a research where the initial data collection is quantitative, which is then followed by qualitative data. The data collection instrument is in the form of a response questionnaire for the STAD and NHT learning models with 18 statements, student interest questionnaires of 11 statements, and learning outcomes test sheets containing 7 questions. Furthermore, the data were analyzed by descriptive statistics to find the average value and using inferential statistics in the form of multiple regression and ANOVA tests to see quantitative data, while for qualitative data using Miles Huberman, namely data reduction, data display, and conclusions. This study uses 327 students of SMK 1 and SMK 4 in Jambi City by using a total sampling technique, namely the entire population is used as the research sample. Then interviewed 20 students who were willing to conduct interviews. The results of this study indicate that Student responses to the STAD learning model have a good category, which is 60.2% (197 of 327) and student responses to the NHT learning model of teacher pedagogic competence have a low category. good that is equal to 58.7% (192 of 225). Student interest in learning also has a good category of 60.9% (199 out of 327). There is a significant influence between learning models, interests, and student learning outcomes, with the determination coefficient value of (R2) 0.729. This means the contribution of the learning model and student interest in student learning outcomes by 72.9 %, while other variables influence the remaining 27.1 %.